Pulmonary Alveolar Microlithiasis Associated with Calcifications in the Seminal Vesicles - Arslan A.; Yalin T.; Akan H.; Belet U. (My University, 1996)
Pulmonary alveolar microlithiasis is an inherited disorder of unknown etiology. It is a rare disease characterized by calcified intraalveolar microgranules. Several hypotheses on the etiopathogenesis have been put forward, such as increased intestinal calcium resorption and retention. This case report of pulmonary alveolar microlithiasis is associated with punctate calcifications in the seminal vesicles.
Keywords: Lung, Calcification